Perbandingan Cadangan Ovarium Sebelum Dan Setelah Tindakan Laparoskopi Kistektomi â€œFertility Sparingâ€ Pada Penderita Kista Endometriosis - Rizary, Dwinda; Hendry, Dedy (Fakultas Kedokteran Universitas Andalas, 2020)
Laparoscopy Cystectomy still remains the first line as the treatment of endometriosis cyst. A â€œfertility sparingâ€ laparoscopy is a procedure that preserve uterus and ovaries of endometrioma patient. Objective: was to compare the ovarian reserve before and after laparoscopic cystectomy â€œfertility sparingâ€ using three marker of ovarian reserve which are AMH, FSH and Estradiol on 2nd or 3rd day of menstrual period and counting the AFC by Transvaginal Ultrasound.Methods: This study is an experimental study on 25 endometrioma patient. Ovarian reserve values was taken before and after laparoscopy using three markers which are AMH, FSH and Estradiol and AFC. All patient included to group performed laparoscopy cyctectomy with several techniques which are no or less use of electrocoagulation, using vassopresin injected to the cyst wall, using stripping of the membrane technique on cyst, without suturing, using compression to control bleeding, avoiding hillus cut. Statistical Analysis was using paired t test method.Result: There was average differences on AMH value before 1,77 Â± 0,39 ng/ml and after laparoscopy 1,54 Â± 0,38 ng/ml. FSH value before was 6,91 Â± 4,59 mlU/ml and after was 10,13 Â± 6,51 mlU/ml, for estradiol before was 99,65 Â± 77,18 mlU/ml and after was 63,67 Â± 35,22 mlU/ml. There were 15 samples before laparoscopy has AFC <4, 10 samples has AFC 4-6, after laparoscopiy there was 8 samples has 8 AFC, 8 samples has 4-6 AFC, and 9 samples has 7-10 AFC. There was a statistical significance on the reduce of ovarian reserve before and after laparoscopic cystectomy â€œfertility sparingâ€ (p=0,001).Conclusion: There was the affect of laparoscopy cystectomy to the decrease of ovarian reserve which sre 13% decreaed of AMH (p+0,001), 31,6% increased of FSH (p=0,001), estradiol was 47,8% decreaed (p=0,001) and AFC has increased 47.9% (p=0,003). Keywords: Laparoscopic Cystectomy, Endometriosis, Anti Mullerian Hormone, Antral Follicle